Relationship Between Cancer and Microbiota - Çiltaş, Arzuhan Çetindağ; Yılmaz, Feride Taşkın (International Journal of Human and Health Sciences (IJHHS), 2020)
Microbiota might be considered as an environmental factor which we are always exposed to at high doses lifelong. It also includes bacteria and other organisms (fungus, protozoa, virus and etc.) existing and living in our gastrointestinal tract and other anatomic regions (mouth, skin, vagina). After it has been indicated that microbiota is related with human health and many diseases such as cancer, studies in this field have gained speed and in view of the fact that microbiota should be assessed as a new organ in our body has emerged. Microbiota protects tissues from antigens and pathogens by strengthening mucosal barrier. Cancer and inflammatory disorders increase when the barrier is destroyed. When the barrier is destroyed, microbes might affect immune reactions in growing tumor microenvironments more by forming proinflammatory or immunosuppressant programs. Microbiota which accompanies intestinal and epithelial surface of human body affects starting and growing of the cancer and impact of cancer treatment on tumor cells by intervening systemic metabolism, immune system and inflammations. Many factors including environmental conditions such as host genetics and diet regulate microbiota diversity and ultimately regulate carcinogenesis and cancer treatment. In this review, we planned to emphasize importance of the relation between microbiota and cancer which has been an important subject of scientific researches in recent years. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 251-256